2020
DOI: 10.1136/jech-2020-214496
|View full text |Cite
|
Sign up to set email alerts
|

Ageing trajectories of health—longitudinal opportunities and synergies (ATHLOS) Healthy Ageing Scale in adults from 16 international cohorts representing 38 countries worldwide

Abstract: BackgroundUniform international measurement tools for assessing healthy ageing are currently lacking.ObjectivesThe study assessed the novel comprehensive global Ageing Trajectories of Health: Longitudinal Opportunities and Synergies (ATHLOS) Healthy Ageing Scale, using an Item Response Theory approach, for evaluating healthy ageing across populations.DesignPooled analysis of 16 international longitudinal studies.Setting38 countries in five continents.SubjectsInternational cohort (n=355 314), including 44.4% (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The HAI was measured using a healthy aging scale (BMRM-D-18-00329) developed by the Aging Trajectories of Health: Longitudinal Opportunities and Synergies (ATHLOS) project ( 32 ), which consisted of 16 general population longitudinal studies ( 33 ). Item response theory model was used to develop an ATHLOS scale with 41 items for measuring healthy aging ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…The HAI was measured using a healthy aging scale (BMRM-D-18-00329) developed by the Aging Trajectories of Health: Longitudinal Opportunities and Synergies (ATHLOS) project ( 32 ), which consisted of 16 general population longitudinal studies ( 33 ). Item response theory model was used to develop an ATHLOS scale with 41 items for measuring healthy aging ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the scale against sociodemographic, health factors and mortality has shown that this score corresponds well with health status and could be useful in international ageing studies [4]. Details on the construction of the scale and its performance have been widely presented and discussed in earlier publications [4,5]. Scale values follow a normal distribution of a mean of 50 and a standard deviation of 10 where higher values mean better healthy ageing.…”
Section: Measurements Of Healthy Ageingmentioning
confidence: 98%
“…), and activities of daily living (getting in or out of bed, bathing, getting dressed, using the toilet, eating, shopping, preparing meals, housework, etc.) that imply interaction with the individual's environment [5].…”
Section: Measurements Of Healthy Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, with this approach, researchers may investigate the impact of disease burden in healthy aging which would not be possible if the presence of a disease or a biomarker that is associated with it was part of the metric itself. As a result, such metrics can be used in complex models that will include socioeconomic, biological and clinical factors in order to identify potential determinants of healthy aging ( 10 13 ).…”
Section: Disease Burden Vs Functional Abilitymentioning
confidence: 99%